[PP.26.02] FREE VERSUS FIXED COMBINATION ANTIHYPERTENSIVE THERAPY FOR ESSENTIAL ARTERIAL HYPERTENSION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (September 2016) - Mallat, S.; Tanios, B.; Itani, H.; Loutfi, T.; Akl, E.
Abstract : Objective: Most patients with arterial hypertension (HTN) require more than one blood pressure (BP)-lowering drug to achieve BP target. In a free drug combination, each BP-lowering drug is administered as a separate pill, while in a fixed drug combination, BP-lowering drugs are combined in a single pill. The objective of this systematic review is to compare the beneficial and harmful effects of using a fixed versus free combination of BP-lowering agents in patients with essential HTN. Design and method: We conducted a comprehensive search that included the Cochrane CENTRAL, MEDLINE, and EMBASE. We included randomized clinical trials (RCTs) addressing the objective of the review and assessing at least one of the following outcomes: BP-lowering efficacy, rapidity in achieving BP target, compliance, incidence of side effects, mortality, and morbidity outcomes. Two review authors independently and in duplicate selected eligible studies then abstracted relevant information and assessed risk of bias using standardized data extraction forms. The primary meta-analyses used a random-effects model. Results: We identified seven eligible RCTs with a total of 397 participants. Meta-analysis for the pre-specified outcome of efficacy in controlling BP showed a non-significant reduction of mean systolic BP of 0.81 mmHg (95% CI -3.25, 1.64) favoring the fixed combination group. As for the outcome of adverse events, meta-analysis results showed a non-significant 13% risk reduction favoring the free combination group (risk ratio 1.13, 95% CI 0.85, 1.5). Quality of evidence was low for both outcomes. Rapidity in achieving BP target was assessed in one trial, and the results favored the fixed combination group. Adherence to treatment was assessed in three trials, no pooled analysis was possible due to either missing data or differences in the methods of outcome measurement. The included trials were short term, none assessed mortality and morbidity. Figure. No caption available. Conclusions: The available low quality evidence does not confirm or rule out a substantive difference in benefits or harms between fixed combination and free combination of anti-hypertensive regimen in the management of patients with HTN. Well designed RCTs with a long duration of follow-up and assessment of morbidity and mortality outcomes are needed.